Writing the Republic: liberalism and morality in American political fiction - Hutchison, Anthony (2004)
This thesis deploys works of literature, political theory and intellectual history to reach an understanding of both the specific form and the content taken by the American political novel. This understanding is informed by an over-arching analysis of liberalism as the dominant ideology within the US political tradition and the pressure, moral and political, exerted on this ideology by successive counter-ideologies at various historical junctures.